Shared Space: Rethinking the U.S.-Mexico Border Environment - Santés, Ricardo (Frontera Norte, 2017)
Lawrence A. Herzog (editor) La Jolla, Center for U.S.-Mexican Studies, University of California, San Diego, 2000, 375 pp.